Performance Study of Buried Pipelines under Static Loads - Alanazi, Mahdi J.; Qinghua, Yang; Al-Bukhaiti, Khalil (Civil Engineering Journal, 2022)
The possibility of servicing lifelines such as highways, railways, pipelines, and tunnels is of great social importance. The characteristic that separates the buried pipeline from other structures is that its dimensions are very long compared to its other dimensions. Ground vibrations caused by earthquakes, construction activities, traffic, explosions, and machinery can damage these structures. Lifeline integrity can be compromised in two ways: (1) direct damage due to excessive dynamic loading of the lifeline, and (2) indirect damage due to soil failures such as liquefaction, slope instability, and differential settlements. 3D printing (also known as additive manufacturing) is an advanced manufacturing process that can automatically produce complex geometric shapes from a 3D computer-aided design model without tools, molds, or fixtures. This automated manufacturing process has been applied in diverse industries today because it can revolutionize the construction industry with expected benefits. This research study on the performance of buried pipelines under static loads to the structure's safety against the possible development of progressive failure. This research study includes a numerical study, where it was studied many parameters to value the performance of the pipeline. The parameters are (a) the material of the pipeline (steel, traditional concrete, and 3D concrete printed), (b) the thickness of the pipeline (20, 30, and 40 mm), and (c) soil type (moist sandy soil, saturated sandy soil, moist cohesive soil, and saturated cohesive soil). Different results were obtained depending on the type of soil where all pipelines materials' behavior was similar in the case of moist soil.Â Doi: 10.28991/CEJ-2022-08-01-01 Full Text: PDF